2015
DOI: 10.1371/journal.pone.0122764
|View full text |Cite
|
Sign up to set email alerts
|

15-Deoxy-Δ12,14-Prostaglandin J2 Inhibits Osteolytic Breast Cancer Bone Metastasis and Estrogen Deficiency-Induced Bone Loss

Abstract: Breast cancer is the major cause of cancer death in women worldwide. The most common site of metastasis is bone. Bone metastases obstruct the normal bone remodeling process and aberrantly enhance osteoclast-mediated bone resorption, which results in osteolytic lesions. 15-deoxy-Δ12,14-prostaglandin J2 (15d-PGJ2) is an endogenous ligand of peroxisome proliferator-activated receptor gamma (PPARγ) that has anti-inflammatory and antitumor activity at micromolar concentrations through PPARγ-dependent and/or PPARγ-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(44 citation statements)
references
References 45 publications
1
42
0
1
Order By: Relevance
“…To understand the effect of PPARγ on alveolar bone remodelling during the periodontitis progression, we detected bone metabolism‐related factors by ELISA and immunohistochemistry and investigated the loss of alveolar bone by several methods. Using RGZ to activate PPARγ for 4 weeks, promoted the expression of ALP and BMP‐2, and reduced the RANKL/OPG ratio in serum, which were consistent with the findings in previous studies (Kim et al., ; Koufany et al., ). Nevertheless, after 8 weeks the results reversed with the decreased expression of ALP, BMP‐2 and the increased RANKL/OPG ratio with RGZ intervention.…”
Section: Discussionsupporting
confidence: 90%
“…To understand the effect of PPARγ on alveolar bone remodelling during the periodontitis progression, we detected bone metabolism‐related factors by ELISA and immunohistochemistry and investigated the loss of alveolar bone by several methods. Using RGZ to activate PPARγ for 4 weeks, promoted the expression of ALP and BMP‐2, and reduced the RANKL/OPG ratio in serum, which were consistent with the findings in previous studies (Kim et al., ; Koufany et al., ). Nevertheless, after 8 weeks the results reversed with the decreased expression of ALP, BMP‐2 and the increased RANKL/OPG ratio with RGZ intervention.…”
Section: Discussionsupporting
confidence: 90%
“…The OVX mice after treatment with aliskiren in this study displayed the decreased bone resorption as demonstrated by the reduced excretion of urinary calcium and the decreased level of serum TRAP; moreover, aliskiren could markedly reduce the TRAPpositive osteoclasts number in trabecular bone and downregulate the expression of osteoclast-specific genes, including carbonic anhydrase II (CAII), matrix metalloproteinase (MMP)-9, and Cathepsin K. MMP-9 is the enzyme secreted from the ruffled border of osteoclasts to dissolve the organic components of bone, and CAII in osteoclasts is responsible for dissolving the bone inorganic substance [29]. Cathepsin K, one of proteolytic enzymes, degrades organic components in the bone matrix [46]. Therefore, the present study revealed that the inhibition of aliskiren on bone resorption via suppressing the osteoclastogenesis and the osteoclastic resorptive activity might be the potential mechanism for the beneficial effects of aliskiren on trabecular bone of OVX mice.…”
Section: Discussionmentioning
confidence: 99%
“…After 24 h, each wound area was photographed. The width of the wound area was measured using ImageJ software, and the percentage of wound closure was derived by using the following formula as previously described: [1 -(final wound width/initial wound width)] x 100 [26].…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
“…Clear zones against the blue background indicate the gelatinolytic activity of MMPs. Cathepsin K levels in the culture media were determined using a SensiZyme cathepsin K activity assay kit (Sigma-Aldrich) according to the manufacturer's instructions [26].…”
Section: Gelatin Zymography and Cathepsin K Assaymentioning
confidence: 99%